From Molecules to Materials: Computational Design of N‐Containing Porous Aromatic Frameworks for CO2 Capture. Issue 9 (23rd June 2014) - Li, Wenliang; Shi, Haijie; Zhang, Jingping
Abstract Porous aromatic frameworks (PAFs) are novel materials with diamond topology. With the aim of enhancing their CO2 capture and storage capacity and investigating the effect of nitrogen and/or ‐COOH decorations on CO2 adsorption in PAFs, a series of N‐containing PAFs were designed based on ab initio results. The interaction energies (Eint) between CO2 and each six‐membered ring were calculated at the B2PLYP‐D2/def2‐TZVPP level, then the six‐membered rings with high CO2‐binding affinity were selected and used in the PAFs. To explore the performance of the designed PAFs, the CO2 uptake, selectivity of CO2 over CH4, H2, and N2, and the Eint value of CO2 in PAFs were investigated by using grand canonical Monte Carlo (GCMC) simulations and ab initio calculations. This work shows that pyridine with one nitrogen atom can provide a strong physisorption site for CO2, whereas more nitrogen atoms in heterocycles will reduce the interaction, especially at relatively low pressure. PAFs with COOH groups show high CO2 capacity. Our work provides an efficient way to understand the adsorption mechanism and a supplemental approach to experimental work.